استراتيجيات الاستثمار خارج قطاع المحروقات في الجزائر واقـــــــع و تحديــــات - خشخوش, يسمينة; رضواني, رشيد; فرحات, عثمان (جامعة الوادي university eloued, 2017)
يعتبر الاستثمار الأجنبي المباشر من اهم مصادر تمويل التنمية كمصدر بديل للقروض الخارجية ذات الأثر السلبي ،اذ تنافست الدول لاجتذابه من خلال تحسين مناخها الاستثماري و سن قوانين تشجعه و تضمن حمايته و انتهاج سياسات اقتصادية و مالية متكاملة تسير المناخ الاستثماري بصفة عامة و الاستثمار الأجنبي بصفة خاصة ،و تختلف سياسات الاستثمار الأجنبي المباشر من دولة الى أخرى باختلاف طبيعة اقتصادها ،و الجهود المبذولة لاجتذابه بالقدر الذي يساعدها على تمويل اقتصادها و تنميته. وتعد الاستراتيجيات الاستثمارية المنتهجة في الجزائر وهو موضوع دراستنا هذه، غير كافية لجذب الاستثمار الأجنبي -على الرغم من تعددها وتوفرها بالقدر الكافي لتشجيع المستثمرين-اذ هناك ما يعيق فعاليتها بدءا بمكونات المناخ الاستثماري والتي لاتزال تعاني نقصا واضحا كالبنية التحتية والمؤسسية والتي اثرت بشكل مباشر على حصص تدفقات الاستثمارات الامر الذي يعود الى عجزها عن توجيه تلك الاستراتيجيات لخدمة اقتصادها كون غالبيتها موجهة لقطاع المحروقات. Foreign direct investment is considered one of the most important sources of financing for development as an alternative source of foreign loans with a negative impact. Countries competed to improve their investment climate, enact laws that encourage and guarantee their protection, and pursue integrated economic and financial policies. The investment climate in general and foreign investment in particular , Foreign direct investment policies differ from country to country depending on the nature of their economy, and efforts to attract them to the extent that they help them finance their economy and development. The investment strategies adopted in Algeria, which is the subject of our study, are not sufficient to attract foreign investment - despite the multiplicity and availability of them to encourage investors - as there is an impediment to its effectiveness starting with the components of the investment climate, which still suffer a clear shortage such as infrastructure and institutional, which directly affected the quotas Investment flows, which is due to its inability to direct these strategies to serve its economy, the majority of which is directed to the hydrocarbons sector
مذكروة ماستر اقتصاد عمومي
Keywords: : الاستثمار الأجنبي المباشر، الاقتصاد الجزائري، المناخ الاستثماري سياسات واستراتيجيات الاستثمار الأجنبي المباشر.; Direct foreign investment, Algerian economy, investment Investment climate policies and strategies direct foreign investment